2021
DOI: 10.3390/gels7040175
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Chitosan-Pectin Hydrogels: From Rheological Characterization to Scaffold Development and Assessment

Abstract: Chitosan-pectin hydrogels were prepared, and their rheological properties were assessed in order to select the best system to develop scaffolds by 3D printing. Hydrogels showed a weak gel behavior with shear thinning flow properties, caused by the physical interactions formed between both polysaccharides, as observed by FTIR analysis. Since systems with high concentration of pectin showed aggregations, the system composed of 2 wt% chitosan and 2 wt% pectin (CHI2PEC2) was selected for 3D printing. 3D printed sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 59 publications
1
20
0
1
Order By: Relevance
“…Despite being possible to print scaffolds with the chitosan hydrogel, the structures obtained did not match the desired quality. One of the major limitations when using only chitosan to print 3D structures is the lack of mechanical properties that have been reported in previous studies [ 25 , 28 , 37 , 38 ]. Thus, to enhance the final printability and improve the mechanical properties of chitosan, some authors suggest the addition of other materials to the chitosan [ 21 ], such as starch [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being possible to print scaffolds with the chitosan hydrogel, the structures obtained did not match the desired quality. One of the major limitations when using only chitosan to print 3D structures is the lack of mechanical properties that have been reported in previous studies [ 25 , 28 , 37 , 38 ]. Thus, to enhance the final printability and improve the mechanical properties of chitosan, some authors suggest the addition of other materials to the chitosan [ 21 ], such as starch [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations have shown that the addition of other polymers to chitosan has resulted in better results in terms of printability [ 38 ], more specifically related to the combination of starch [ 25 ]. However, these investigations lack information associated with the optimal values and printing conditions necessary to produce the chitosan–starch hydrogels and the scaffolds.…”
Section: Resultsmentioning
confidence: 99%
“…However, the inhomogeneity of the resulting hydrogels is still an issue; advancements towards improving the homogeneous distribution of electrostatic forces have been achieved through acidification of the mixture in the vapor phase, for example by resorting to CHT and pectin [ 166 ]. CHT-pectin hydrogels were optimized for 3D-printed scaffold production for regenerative medicine [ 167 ].…”
Section: Chitosan-based Hydrogels For Biomedical Applicationsmentioning
confidence: 99%
“…Chitosan-based physical hydrogels are produced by ion-complex formations with negatively charged molecules such as dicarboxylic acids [ 58 ], citric acid (tricarboxylic acid) [ 59 ], sulfates, phosphates [ 60 ], gallic acid [ 61 ], alginate [ 62 , 63 , 64 , 65 ], pectin [ 66 , 67 ], sulfoethyl cellulose [ 68 ], and hyaluronic acid [ 69 ]. Through the physical interaction between anions of these molecules and cations of chitosan hydrogels can be formed.…”
Section: Gelation Techniques Of Chitosan-based Hydrogelsmentioning
confidence: 99%